Design, development and performance evaluation of garlic bulb (Allium sativum) breaker for planting material production - CHANNABASAMMA, B B; RATHINAKUMARI, A CAROLIN; KUMARAN, G SENTHIL (The Indian Journal of Agricultural Sciences, 2015)
Garlic (Allium sativum L.) is one of the important bulb crops grown and used as a spice in culinary ingredient as it adds to the taste and flavour in a wide range of food preparations. It also has medicinal properties. Garlic is propagated by single clove. Conventionally, garlic cloves are separated by rubbing the bulb between palms, against jute bags or by beating with a wooden stick. These methods are very laborious and time consuming. Hence, a garlic bulb breaker to break and separate cloves from the whole garlic bulb was designed and developed. The garlic bulb breaker consisted of feeding chute, rubber padded rollers (two stages), blower, outlets for cloves and skins, main frame, power and power transmission system. The garlic bulb breaker was evaluated with three types of rubber padding material: plain-plain, button-button and corrugated-corrugated, four clearances between the rollers: 15, 18, 21 and 24 mm and three peripheral speed of rollers: 25.92, 34.56 and 43.2 m/min. Germination experiments were conducted to study the quality of garlic cloves as planting material with the garlic cloves separated by the machine. Highest breaking efficiency of 75% was obtained with corrugated type rubber padding material at an optimum clearance of 18-21 mm clearance between rollers and at 43.2 m/min peripheral speed of rollers. Minimum damage of 0 to 0.7%% and clove loss of 1.08% were observed at optimized parameters. The garlic cloves separated by the developed machine had 100% germination. The breaking capacity of machine was 195 kg/hr. The operating cost of the machine Rs.` 0.3/kg against Rs.` 2.25/kg by manual clove separation.